Bacteriostatic and bactericidal activities of beta-lactam antibiotics enhanced by the addition of low concentrations of gentamicin. - Masuda, G (1980)
The combined effects of low concentrations of gentamicin on certain beta-lactam antibiotics were studied by the agar plate method. the combination of gentamicin with cephalothin produced synergism against 17 of 26 strains of Escherichia coli and 19 of 27 strains of Klebsiella sp. if assessed at the bacteriostatic (minimal inhibitory concentration) level. Synergy against many more strains was apparent when bactericidal concentrations were used. Synergy against most of these strains was observed if bactericidal concentrations with brief exposure times (3 h) to the antibiotics were used for measurement. Additive effects were observed in almost all of the remaining strains. The combination of gentamicin and carbenicillin were synergistic against most strains of Pseudomonas aeruginosa when any bacteriostatic or bactericidal measurement was used as the criterion.